NOTHING TO REPORT? MOTIVATIONS FOR NON-DISCLOSURE OF SOCIAL ISSUES BY INDONESIAN LISTED COMPANIES - Roman Cahaya , Fitra; A Porter , Stacey; M Brown, Alistair (The journal of contemporary issues in business and government, 2006)
A study based on the extent of voluntary social disclosure practices of Indonesian listed entities using Global Reporting Initiatives as a simplified social disclosure index found that all Jakarta Stock Exchange listed entities voluntarily disclose some social information in their annual reports, but at a low level (14.15%). Stakeholder theory partially explains the disclosures but does not explain why some issues such as Child Labour, Forced and Compulsory Labour, Bribery and Corruption and Political Contributions are not disclosed by any listed companies. This paper examines the motivations for these non-disclosures and suggests that one of the more likely reasons that companies do not disclose certain items is to avoid scrutiny, particularly on issues where they are not performing or where it is evident that they are in breach of government regulations.